Assessment of social function in four-year-old children with cerebral palsy. (April 2013) - McFadd, Emily; Hustad, Katherine C.
<x xml:space="preserve">Abstract</x> Objective: To determine whether scores from the social function domain of the Paediatric Evaluation of Disability Inventory (PEDI) would reflect differences among speech–language profile groups for children with cerebral palsy (CP). Methods: Thirty-four children with CP participated (mean age = 54.4 months). PEDI social function raw scores, developmentally stratified skill levels, and types of skills mastered at a 75% criterion level were examined. Results: Significant differences were observed in social function scores overall and within early and age-appropriate skills among all profile groups with one exception. Skill mastery varied based on profile group and on developmental age category of each skill. Conclusions: The PEDI appears to capture language delay in children with CP, but it may not be sensitive to the impact of speech intelligibility deficits on social function. Findings call for the development of a new tool that more accurately assesses communicative activities and participation in children with CP.